2017
DOI: 10.3389/fimmu.2017.00075
|View full text |Cite|
|
Sign up to set email alerts
|

Agonistic Anti-PDGF Receptor Autoantibodies from Patients with Systemic Sclerosis Impact Human Pulmonary Artery Smooth Muscle Cells Function In Vitro

Abstract: One of the earliest events in the pathogenesis of systemic sclerosis (SSc) is microvasculature damage with intimal hyperplasia and accumulation of cells expressing PDGF receptor. Stimulatory autoantibodies targeting PDGF receptor have been detected in SSc patients and demonstrated to induce fibrosis in vivo and convert in vitro normal fibroblasts into SSc-like cells. Since there is no evidence of the role of anti-PDGF receptor autoantibodies in the pathogenesis of SSc vascular lesions, we investigated the biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 53 publications
(59 reference statements)
1
28
0
Order By: Relevance
“…The IL-33 receptor consists of the heterodimeric complex of ST2 and the IL-1 receptor accessory protein, the former of which has been determined to be selectively expressed in Th2 immune responses ( 3 ). Additionally, recent studies have determined a higher prevalence in the development of colorectal cancer amongst patients with inflammatory bowel disease, which appeared to be mediated, at least partially, by elevated levels of IL-33 and ST2 expression under the inflammatory state of the disease ( 8 , 9 , 11 , 21 , 22 ). A previous study determined an association between increased IL-33 expression and increased angiogenesis in vivo , indicating that the IL-33 signaling pathway may support carcinogenesis ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IL-33 receptor consists of the heterodimeric complex of ST2 and the IL-1 receptor accessory protein, the former of which has been determined to be selectively expressed in Th2 immune responses ( 3 ). Additionally, recent studies have determined a higher prevalence in the development of colorectal cancer amongst patients with inflammatory bowel disease, which appeared to be mediated, at least partially, by elevated levels of IL-33 and ST2 expression under the inflammatory state of the disease ( 8 , 9 , 11 , 21 , 22 ). A previous study determined an association between increased IL-33 expression and increased angiogenesis in vivo , indicating that the IL-33 signaling pathway may support carcinogenesis ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, GKT-137831 was also able to reduce collagen gel contraction as well as expression of alpha-SMA and CCN2 protein overexpression in fibroblasts isolated from dermal lesions in SSc patients ( 41 ). A NOX4-derived increase of ROS has also been reported to be involved in the vascular smooth muscle cells contractile to synthetic phenotype switch elicited by agonistic anti-PDGF receptor autoantibodies from SSc patients ( 69 ) Taken together, these findings indicate that the NOX system, in addition to ROS production, mediates the activation of collagen synthesis and profibrotic genes.…”
Section: Introductionmentioning
confidence: 88%
“…Trade name Target Type of tumour Imatinib Glivec Abl, PDGFRs, Kit CML, GIST beneficial effect may also involve inhibition of other kinases than those of PDGF receptors. It has been suggested that systemic sclerosis is promoted by activating autoantibodies against PDGFRa found in the serum of patients [97][98][99]; however, this observation has been questioned in other studies [100][101][102].…”
Section: Drugmentioning
confidence: 99%